The impact of COVID-19 pandemic on air particulate matter exposure and heart attacks: a 5-year retrospective cohort study in Taiwan (2017–2021) - Yen, Chih-Chien; Hsiao, Po-Jen; Chu, Chi-Ming; Chen, Ping-Ling (Frontiers in Public Health, 2024)
Background Heart attacks including acute ST-segment elevation myocardial infarction (STEMI) and acute decompensated heart failure (ADHF) caused from the particulate matter (PM) and air pollutant exposures are positively associated with regional air pollution severity and individual exposure. The exceptional coronavirus disease epidemic of 2019 (COVID-19) may enhance the air conditions in areas under COVID-19 pandemic. We sought to study the impact of COVID-19 pandemic on air particulate matter (PM) exposure and heart attacks in Taiwan. Methods This retrospective cohort study was conducted in one teaching hospital in Taichung, Taiwan. We examined emergency patients diagnosed with acute STEMI and ADHF from January 1, 2017, to March 31, 2020, (i.e., before the COVID-19 pandemic) and from April 1, 2020, to December 31, 2021, (after the COVID-19 pandemic). The effects of particulate matter with a diameter of less than 2.5 micrometers (PM2.5) and PM10 as well as temperature and humidity on environmental air pollutants were recorded. The analysis was performed with a unidirectional case-crossover research design and a conditional logistic regression model. Results Both PM2.5 and PM10 levels had a positive association with the risk of acute STEMI before the COVID-19 pandemic (PM2.5 adjusted odds ratio (OR): 1.016, 95% confidence interval (CI): 1.003–1.032 and PM10 adjusted OR: 1.009, 95% CI: 1.001–1.018) and ADHF (PM2.5 adjusted OR: 1.046, 95% CI: 1.034–1.067 and PM10 adjusted OR: 1.023, 95% CI: 1.027–1.047). Moreover, the results demonstrated that PM2.5 and PM10 were not associated with the risk of acute STEMI or ADHF after the COVID-19 pandemic. Reduction in PM2.5 and PM10 levels after the COVID-19 pandemic were noted. Hospital admissions for acute STEMI (7.4 and 5.8/per month) and ADHF (9.7 and 8.2/per month) also decreased (21.6 and 15.5%) after the COVID-19 pandemic. Conclusion In Taiwan, paradoxical reductions in PM2.5 and PM10 levels during the COVID-19 pandemic may decrease the number of hospital admissions for acute STEMI and ADHF. As the COVID-19 pandemic eases, the condition of air pollution may gradually become worse again. The governments should formulate better policies to improve the health of the public and the quality of the air.